Evaluating the Long-Term Neurologic Sequelae Among Trauma Patients who Received Flexion-Extension Radiographs: Flexion-Extension Radiographs - Durler, Shelby; Lightwine, Kelly; Ablah, Elizabeth; Cox, Thomas; Haan, James M (Kansas Journal of Medicine, 2024)
Introduction. This study evaluated the presence of neurologic sequelae among trauma patients after flexion-extension (F/E) radiographs. Methods. Authors of the study conducted a retrospective review of patients (age ≥ 14 years) with a Glasgow Coma Score of 15 who sustained a blunt traumatic injury and received F/E radiographs. Radiographic scans were defined as positive, negative, inconclusive, or incomplete. The neurologic status of each patient was assessed before and after the F/E radiographs, and at discharge and follow-up.Results. Of the 501 patients included in the analysis, 84.6% (n = 424) had negative F/E radiographs, and 3.2% (n = 16) had positive F/E radiographs. Ten percent (n = 51) of patients had incomplete F/E radiographs, and 2.0% (n = 10) were inconclusive due to the inability to rule out a ligamentous injury. Three patients (0.6%) had MRI-confirmed ligamentous injuries, all of which had initial incomplete F/E radiographs due to pain. No patient had a documented neurological deficit before or after the F/E exam. Three patients with an initial negative F/E radiograph returned to the clinic with symptoms of neurologic sequelae. Two of these patients had symptom resolution with no further issues at future follow-up appointments. The third patient was found to have chronic neurologic symptoms after further evaluation.Conclusions. The inclusion of F/E exams in cervical spine clearance protocols did not demonstrate any new long-term iatrogenic neurologic injuries. Consideration should be given to performing MRIs on patients with incomplete F/E radiographs that cannot rule out a ligamentous injury.